2004
DOI: 10.1002/ijc.20253
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin‐like growth factor (IGF)‐I and IGF‐binding protein 3 and the risk of premenopausal breast cancer: A meta‐analysis of literature

Abstract: Biologic evidence suggests substantial effect of insulin-like growth factor (IGF)-I in mammary cell carcinogenesis. However, controversy remains regarding the association between circulating IGF-I levels and the risk of premenopausal breast cancer in epidemiologic studies. In addition, the association of IGF-binding protein (IGFBP)-3, which binds with and modifies the effect of IGF-I, is unclear. To clarify these associations, we performed a meta-analysis of all the published studies. A systematic review of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
63
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 26 publications
0
63
3
2
Order By: Relevance
“…3,4 From the present pooled analyses, we found that higher concentrations of IGF1 were significantly associated with an increased risk of pre-menopausal breast cancer but not of post-menopausal breast cancer, which was consistent with previously published studies. 4,39,40 It was reported that estrogen could interact with IGF1 to increase cell proliferation, particularly in breast cancer cells. 41 In addition, both estrogen 42 and IGF1 levels were higher in pre-menopausal breast cancer than those in post-menopausal breast cancer, suggesting that IGF1 might have a different role in pre-and postmenopausal breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 From the present pooled analyses, we found that higher concentrations of IGF1 were significantly associated with an increased risk of pre-menopausal breast cancer but not of post-menopausal breast cancer, which was consistent with previously published studies. 4,39,40 It was reported that estrogen could interact with IGF1 to increase cell proliferation, particularly in breast cancer cells. 41 In addition, both estrogen 42 and IGF1 levels were higher in pre-menopausal breast cancer than those in post-menopausal breast cancer, suggesting that IGF1 might have a different role in pre-and postmenopausal breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The authors performed their meta-analysis based on 6 studies and concluded that there were marginally significant associations with IGF-I concentrations but no associations with IGFBP-3 concentrations. We repeated these analyses and discovered that there were major discrepancies between the 95% CIs listed by Sugumar et al 3 and those stated within the individual studies (Table I). Specifically, the 95% CIs used in Table II and the forest plots of their report were considerably wider than those reported by the original studies, probably reflecting a miscalculation during log transformation.…”
mentioning
confidence: 92%
“…2,3 At first glance, there are some differences in the results and the derived conclusions. This correspondence addresses the reasons.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…These analyses also took into account potential effects of hyperinsulinemia, by including insulin and leptin, which we show to have no independent associations with breast cancer of their own accord. Serum IGF-I appears to be associated with risk of breast cancer among premenopausal women (7,10,12,13,15,17,24,25), but no similar association has been found among postmenopausal women (10,26). Several explanations for this dichotomy have been proposed.…”
Section: Discussionmentioning
confidence: 99%